Words in noise audiometry in adult subjects with normal hearing - Widayat Alviandi; Jenny Bashiruddin; Brastho Bramantyo; Farisa Rizky (PERHATI-KL, 2020)
Background: Patients with hearing disturbance will generally undergo pure tone audiometry andspeech audiometry in a quiet room, but those examinations cannot evaluate the ability to understand speech in daily environment with a noisy background. Words in noise test will provide valuable informationregarding patient’s hearing problem in noise. Purpose: To evaluate the hearing threshold using wordsin noise test in adults with normal hearing. Method: This cross-sectional study was conducted in CiptoMangunkusumo Hospital from January to April 2017. All subjects who fulfilled the inclusion and exclusioncriteria underwent pure tone audiometry, speech audiometry, and words in noise test. Results: A total of71 individuals with normal hearing were recruited for this study. Words in noise test showed the medianvalue of 67 dB and 100 dB for Speech Recognition Threshold (SRT) 50% and Speech DiscriminationScore (SDS) 100%, respectively. The SRT 50% and SDS 100% were significantly higher in the age group40–60 years compared to the age group 18–39 years. There was also a statistically significant differencebetween males and females at SRT 50% assessed by words in noise audiometry. Conclusion: Wordsin noise test showed a statistically significant difference in SRT 50% and SDS 100% between two agegroups, but no difference was found between genders. The result of this study can be used as a referencefor SRT and SDS values of speech audiometry test in noise.Keywords: words in noise, speech audiometry, speech recognition threshold, speech discrimination score ABSTRAKLatar belakang: Pasien dengan gangguan pendengaran umumnya menjalani pemeriksaanaudiometri nada murni dan audiometri tutur di ruangan yang sunyi, tetapi pemeriksaan ini tidakdapat menggambarkan kemampuan pemahaman wicara di lingkungan sehari-hari yang ramai. Testutur dalam bising dapat mengevaluasi masalah pendengaran pasien dalam keadaan bising. Tujuan:Untuk mengevaluasi ambang pendengaran menggunakan tes tutur dalam bising pada orang dewasadengan pendengaran normal. Metode: Penelitian potong lintang ini dilakukan di Rumah Sakit CiptoMangunkusumo dari Januari hingga April 2017. Semua subjek yang memenuhi kriteria inklusi daneksklusi menjalani pemeriksaan audiometri nada murni, audiometri tutur, dan tes tutur dalam bising.Hasil: Sebanyak 71 orang dengan pendengaran normal diikutsertakan dalam penelitian ini. Tes tuturdalam bising menunjukkan nilai median masing-masing 67 dB dan 100 dB pada Speech RecognitionThreshold (SRT) 50% dan Speech Discrimination Score (SDS) 100%. SRT 50% dan SDS 100% secarasignifikan lebih tinggi pada kelompok usia 40–60 tahun dibandingkan dengan kelompok usia 18–39 tahun. Hasil pemeriksaan tes tutur dalam bising menunjukkan perbedaan yang signifikan antara laki-laki dan wanita pada nilai SRT 50%. Kesimpulan: Tes tutur dalam bising menunjukkan perbedaan yang bermakna secara statistik pada SRT 50% dan SDS 100% antara dua kelompok umur, tetapi tidak ada perbedaan signifikan diantara jenis kelamin. Hasil penelitian ini dapat digunakan sebagai acuan untuk nilai SRT dan SDS pada pemeriksaan audiometri tutur dalam bising.